2012
DOI: 10.1186/2045-9912-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations between blood-brain barrier permeability and matrix metalloproteinases are differently affected by tissue plasminogen activator and hyperoxia in a rat model of embolic stroke

Abstract: BackgroundIn ischemic stroke, blood-brain barrier (BBB) regulations, typically involving matrix metalloproteinases (MMPs) and inhibitors (TIMPs) as mediators, became interesting since tissue plasminogen activator (tPA)-related BBB breakdown with risk of secondary hemorrhage was considered to involve these mediators too. Despite high clinical relevance, detailed interactions are purely understood. After a pilot study addressing hyperoxia as potential neuroprotective co-treatment to tPA, we analyzed interrelatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Strong support for this and our findings are recent data that have shown on one hand that rtPA and NBO, respectively, increases and decreases serum concentrations of matrix metalloproteinase-9, whose expression is known to be critically associated with ischemia-induced disruption of the blood-brain barrier, and on the other hand that combining oxygen and rtPA suppresses the beneficial effects of NBO at decreasing matrix metalloproteinase-9 (30). Based on these findings, the authors suggest as found in the present report that combining NBO and rtPA could not be a safe strategy (30).…”
Section: Lack Of Neuroprotective Action Of Combined Nbo and Rtpasupporting
confidence: 57%
“…Strong support for this and our findings are recent data that have shown on one hand that rtPA and NBO, respectively, increases and decreases serum concentrations of matrix metalloproteinase-9, whose expression is known to be critically associated with ischemia-induced disruption of the blood-brain barrier, and on the other hand that combining oxygen and rtPA suppresses the beneficial effects of NBO at decreasing matrix metalloproteinase-9 (30). Based on these findings, the authors suggest as found in the present report that combining NBO and rtPA could not be a safe strategy (30).…”
Section: Lack Of Neuroprotective Action Of Combined Nbo and Rtpasupporting
confidence: 57%
“…44,294295 An advantage of CORMs is that they deliver CO to tissues with reduced CO-Hb accumulation as compared with inhalation CO. 41,294 CORMs can deliver small amounts of CO in a controlled manner and may represent an experimental therapy for sepsis and inflammatory disorders. 44,294 …”
Section: Therapeutic Stategies Involving Application Of Ho-1 End Prodmentioning
confidence: 99%
“…44, 294297 CORM-1 and CORM-2 have a hydrophobic backbone, whereas CORM-3 is water-soluble and rapidly releases CO in physiological fluids. A water-soluble boron-containing CORM (CORM-A1) has been developed, which slowly releases CO in a pH and temperature-dependent fashion.…”
Section: Therapeutic Stategies Involving Application Of Ho-1 End Prodmentioning
confidence: 99%
“…Acute lung injury (ALI) and its most severe manifestation, acute respiratory distress syndrome (ARDS), is a clinical syndrome characterized by acute hypoxemic respiratory failure, bilateral pulmonary infiltrates on frontal chest radiograph consistent with edema, and normal cardiac filling pressures [ 1 ]. The resulting lung damage can evoke lung failure and multiple organ dysfunctions associated with increased mortality [ 2 ]. Sepsis (the presence of pus-forming bacteria or their toxins in the blood or tissues) is one of the most important ALI/ARDS causes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%